"ADULTING" WITH IBD: A NOVEL, VIRTUAL INFLAMMATORY BOWEL DISEASE TRANSITION PROGRAM FOR TEENS AND CAREGIVERS. (21st January 2021) - Stellway, Jacklyn; Waschmann, Malika; Lin, Henry; Harris, Michael
Abstract: Introduction: Rates of newly diagnosed inflammatory bowel disease (IBD) in pediatric patients increased by 133% from 2007–2016. With the rise comes an increase in patients ultimately transitioning from pediatric to adult GI care. While pediatric care is family-centered and multi-disciplinary adult care is patient-centered with expectation for autonomy. However, less than 15% of patients are fully responsible for their IBD care by late adolescents. The transition period is marked by adverse health outcomes including decreased compliance and increased disease activity and hospitalization. Our data recognized up to 74% of IBD youth reported not having discussed transition at home or with their GI providers, and a desire to receive information in person. Without guidance from the GI team patients may not have adequate time to plan for successful transition. Methods: A one-day 3.5-hour transition preparedness workshop was developed to address the demonstrated need in a pediatric GI clinic. Recruitment letters were distributed to 134 IBD youth ages 15–19. Eighteen consenting participants completed measures prior to and following the workshop (at 3 and 12 months). Assessment tools included previously validated self- and parent-reports: Patient Health Questionnaire-8, General Anxiety Disorder-7), Transition Readiness Assessment Questionnaire, IBD Self Efficacy Scale; and Helping for Health Inventory. Results: While the workshop was designed for in person the pandemic required shift to virtual had strengths and potential drawbacks. Youth across 300 miles were able to attend, as well as IBD young adult peers sharing their personal transition experiences. It is hypothesized pre-workshop data will demonstrate low levels of transition readiness and IBD self-efficacy, with increases in 3- and 12-month post-workshop data. Transition readiness is also presumed to correlate with measures of IBD self-efficacy and miscarried helping by parents. We will present program effectiveness data with factors known to both facilitate and obstruct successful transition from pediatric to adult IBD care. Conclusion: There remains a paucity of literature evaluating the efficacy of IBD transition programs. This research informs such programs by evaluating the efficacy of a one-day virtual workshop on skill development and knowledge. Assessment data and follow up after transition to adult care will provide important information to guide development of evidence-based transition planning for IBD patients.